Emotional Intelligence, Religiosity, and Social Attitude of Students - Rijal Firdaos (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2017)
Students’ low social attitude becomes one of the causes which can lead into immoral actions among students. The aim of this research is to acquire the relationship between emotional intelligence (X1), religiosity (X2), and social attitude of students (Y). The method used in this research is a survey with an instrument of measurement using the questionnaire. The population in this research is 125 students in Islamic Education Department of Tarbiyah Faculty Semester VI in the 2015/2016 Academic Year. The number of samples are 60 students which were chosen by using multi-stage random sampling. The results of research show that there is a significant relationship between emotional intelligence (X1) and social attitude of students (Y), religiosity (X2) and social attitude of students (Y), and between emotional intelligence (X1) and religiosity (X2) with students’ social attitude (Y).